1988
DOI: 10.1093/bja/60.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Toxicity After Treatment With Bleomycin Alone or in Combination With Hyperoxia

Abstract: Female Wistar rats (n = 11) received bleomycin 10 mg kg-1 i.p. three times weekly for 6 weeks. Four weeks later part of the group (n = 7) were exposed to 50% oxygen in air for 4 h; the others served as unexposed controls. A further control group (n = 5) received physiological saline i.p. and was not exposed to oxygen. One week after the hyperoxia treatment all animals were sacrificed and the lungs prepared for histological and biochemical determinations. Although the average body weight of the bleomycin-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…In the current investigation, it was found that BLM did not affect either parameter significantly, notwithstanding its effect on lipid peroxidation. Similar findings have been provided by Blom-Muilwijk et al [14], who reported no change in GSH-Px activity after BLM. In contrast to these findings, however, Karam et al [10]and Phan and Fantone [38]reported an increase in pulmonary GSH-Px activity and a reduced cell content of GSH after BLM administration.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the current investigation, it was found that BLM did not affect either parameter significantly, notwithstanding its effect on lipid peroxidation. Similar findings have been provided by Blom-Muilwijk et al [14], who reported no change in GSH-Px activity after BLM. In contrast to these findings, however, Karam et al [10]and Phan and Fantone [38]reported an increase in pulmonary GSH-Px activity and a reduced cell content of GSH after BLM administration.…”
Section: Discussionsupporting
confidence: 91%
“…In the literature, many experimental protocols have been utilised to induce lung toxicity with BLM, including frequent systemic intraperitoneal injections over long periods of time. The doses of BLM and the frequency of administration as well as the duration of treatment performed in this study have been previously employed by other investigators [14, 15]. It has been reported that after chronic exposure to BLM, body weight loss [14, 33]and an increase in the lung weight/body weight ratio [9, 17]are signs of lung toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because bleomycin is assumed to induce its toxicity partially by the induction of free radicals, the administration of high inspired oxygen could be hazardous. In most studies 64,77,78 carried out in animals, such a relation has been shown. For instance, in hamsters treated with bleomycin and 70% oxygen for 72 h, the mortality was 90% compared with 15% in those animals that received bleomycin only.…”
Section: Risk Factorsmentioning
confidence: 86%